EFEKTIFIVAS PENERAPAN PENELITIAN TINDAKAN KELAS BAGI PROFESIONALITAS GURU DAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: Studi Kasus di SMP Maulana Hasanuddin Cilegon - Ahmad Jauharuddin (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2022)
This research is motivated by the phenomenon that the application of Classroom Action Research in the field of Islamic Religious Education is still not optimal in order to improve and improve the quality of teacher professionalism and the quality of Islamic learning in schools. The purpose of this study was to determine the effectiveness of the implementation of Classroom Action Research for Teacher Professionalism and the quality of Islamic education learning at SMP Maulana Hasanuddin Cilegon. This study uses a qualitative approach using descriptive methods. Data collection techniques were carried out through observation, interviews, and documentation studies. Data analysis was carried out through data reduction, organizing and grouping data, checking, interpreting, and verifying. The results showed that: 1). the application of Classroom Action Research for teacher professionalism is quite effective in improving the quality of learning, 2). The application of teachers through Classroom Action Research in improving the quality of learning can foster teacher motivation to develop their own curriculum, 3). The effectiveness of the teacher's application through Classroom Action Research can improve the ability to understand students, design learning, implement learning, assess/evaluate learning processes and outcomes, and develop the potential of students, 4). The implementation of classroom action research for teacher professionalism is quite good, as can be seen from the teacher's ability to carry out the stages of classroom action research, starting from designing, conducting pre-surveys, planning, implementing, reflecting to evaluating classroom action research.